Comparison of different methods for MP detection: What can we learn from them, and why asking the right question before measurements matters?. (December 2017) - Elert, Anna M.; Becker, Roland; Duemichen, Erik; Eisentraut, Paul; Falkenhagen, Jana; Sturm, Heinz; Braun, Ulrike
Abstract: In recent years, an increasing trend towards investigating and monitoring the contamination of the environment by microplastics (MP) (plastic pieces < 5 mm) has been observed worldwide. Nonetheless, a reliable methodology that would facilitate and automate the monitoring of MP is still lacking. With the goal of selecting practical and standardized methods, and considering the challenges in microplastics detection, we present here a critical evaluation of two vibrational spectroscopies, Raman and Fourier transform infrared (FTIR) spectroscopy, and two extraction methods: thermal extraction desorption gas chromatography mass spectrometry (TED-GC-MS) and liquid extraction with subsequent size exclusion chromatography (SEC) using a soil with known contents of PE, PP, PS and PET as reference material. The obtained results were compared in terms of measurement time, technique handling, detection limits and requirements for sample preparation. The results showed that in designing and selecting the right methodology, the scientific question that determines what needs to be understood is significant, and should be considered carefully prior to analysis. Depending on whether the object of interest is quantification of the MP particles in the sample, or merely a quick estimate of sample contamination with plastics, the appropriate method must be selected. To obtain overall information about MP in environmental samples, the combination of several parallel approaches should be considered. Graphical abstract: Highlights: To establish reliable, harmonized detection methods a combination of several parallel approaches should be considered. Scientific question, what information need to be known about the sample, should be formulated before selecting any methods. Raman scattering can be recognized as the method being the most sensitive to the surface of the particle. TED-GC-MS and SEC allow quantitative and fast assessment of contamination of the studied ecosystem with plastic particles. Abstract : Capsule: The results showed that in selecting the right methodology, the scientific question that determines what needs to be understood is significant, and should be considered carefully prior to analysis.